Digital Co-Parenting in a Suburban Neighbourhood: A Netnographic Study of Whatsapp Group Communication - Damayanti, Nina Afria; Syahriani , Ririn; Fauziah , Nurul Isra; Sitoresmi , Woro Endah (Universitas Negeri Medan, 2025)
Amid the growing integration of digital communication in everyday life, parenting is no longer confined to the private domain of the nuclear family. In many residential settings, particularly in suburban neighborhoods, caregiving has become a collective effort facilitated by digital platforms such as WhatsApp. However, this form of distributed digital parenting remains underexplored, especially within communal cultures like those found in Indonesia. This study aims to explore digital co-parenting practices in a WhatsApp group of residents living in a suburban housing complex in North Sumatra, focusing on the shared supervision of children aged 4–6 who frequently play in communal neighborhood spaces. Conducted from February to March 2025, the research adopted a netnographic approach, collecting data from WhatsApp group conversations, direct observations, and interviews with parents. Thematic analysis was applied and interpreted through the lenses of communities of practice, social capital, and affordance theory. The findings reveal that WhatsApp serves as a key medium for trust-based caregiving, emotional support, and collaborative child supervision. This study contributes to emerging understandings of digital gotong royong in parenting. The article also discusses the study’s implications, limitations, and recommendations for future research.